2008
DOI: 10.1519/jsc.0b013e31815fa038
|View full text |Cite
|
Sign up to set email alerts
|

Noncompatibility of Power and Endurance Training Among College Baseball Players

Abstract: Exercise professionals seeking to develop evidence-based training programs rely on several training principles demonstrated through research and professional experience. In an effort to further research examining these principles, an investigation was designed and completed to evaluate the compatibility of cardiovascular endurance and neuromuscular power training. Sixteen Division-I collegiate baseball players were divided into two training groups with lower body power measured before and after their college p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…In fact, a widespread topic of debate among professionals and researchers is that which addresses the compatibility of distinctive training prescriptions to preferentially elicit adaptation in dissimilar fitness components (e.g., power, strength, speed, cardiovascular endurance, etc.). It has been proposed that, for individuals seeking maximal improvement in a single fitness objective, simultaneous training (i.e., in the same basic time frame) for other fitness parameters should not be performed, because of a potential noncompatibility of the training stimuli (5,51,53). Many professionals believe that, in such situations, the extent of adaptation to one or more fitness attributes could be diminished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a widespread topic of debate among professionals and researchers is that which addresses the compatibility of distinctive training prescriptions to preferentially elicit adaptation in dissimilar fitness components (e.g., power, strength, speed, cardiovascular endurance, etc.). It has been proposed that, for individuals seeking maximal improvement in a single fitness objective, simultaneous training (i.e., in the same basic time frame) for other fitness parameters should not be performed, because of a potential noncompatibility of the training stimuli (5,51,53). Many professionals believe that, in such situations, the extent of adaptation to one or more fitness attributes could be diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Many professionals believe that, in such situations, the extent of adaptation to one or more fitness attributes could be diminished. Most research on this topic of training stimulus ''compatibility'' has proven to be inconsistent, exhibiting the most deleterious affects occurring between simultaneous training for extremely dissimilar fitness components (e.g., aerobic capacity and neuromuscular PP) (25,34,40,51). It has been recently suggested that this interference of strength development during concurrent training may be a result of differential and antagonistic intracellular signaling mechanisms (39).…”
Section: Discussionmentioning
confidence: 99%
“…Vertical jump performance has been shown to accurately evaluate power development in the lower limbs extensor muscles (Samozino et al 2008). It has been suggested that the ability to develop high power output and RFD is more inhibited by combining strength training with high volume endurance training than the ability to produce high force during low muscle shortening velocities; such as for example during a 1RM lift (Dudley and Djamil 1985;Dudley and Fleck 1987;Häkkinen et al 2003;Kraemer et al 1995;Rhea et al 2008). Indeed, Häkkinen et al (2003) did not Wnd any improvement in RFD in the group performing concurrent training despite increased muscle size and 1RM strength, while the group performing only strength training improved peak RFD.…”
Section: Squat Jump and Peak Rfdmentioning
confidence: 99%
“…It has been suggested that training-induced changes in the ability to develop force during high shortening velocities and rate of force development (RFD) are more attenuated than changes in the ability to produce high force during low shortening velocities, when strength training is combined with endurance training (Dudley and Fleck 1987;Rhea et al 2008). Vertical jump power can be assessed in a reliable way during vertical jumping (Samozino et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, endurance training (aerobic) and interval training (anaerobic) will often elicit incompatible results. Rhea et al (16) highlighted a fitness continuum that consists of neuromuscular power, muscular strength, muscular endurance, and cardiovascular endurance when directly discussing metabolic training. Training for the individual components in the fitness continuum will result in differing physiological outcomes.…”
Section: Introductionmentioning
confidence: 99%